QUALITY CONTROL AND SAFETY CHALLENGES IN THE PROCESSING OF TRADITIONAL NIGERIAN KUNU BEVERAGES - admin, S. M. Ibrahim; I. C Igwe; M. A. Dandago; S. A. Jaafar (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Native to Northern Nigeria, Kunu is a fermented, non-alcoholic beverage that is widely consumed. Kunu serves as a drink, a side dish, and a thirst-quenching drink. The kind determines whether it should be served hot or cold. It looks like milky cream and is made with cereal, sugars, and other ingredients. There are currently thirteen types of Kunu in Nigeria. Kunu is rich in nutrients and has probiotic qualities. For inadvertent and / or false reasons, food can be sullied by microorganisms or hurtful substances and cause contaminations, such as food poisoning and toxin-infections Since kunu is typically manufactured in conditions with inadequate quality control, it may serve as a vector for zoonotic and food-borne illnesses such listeriosis, salmonellosis, brucellosis, tuberculosis, shigellosis, and others. It is advised that while preparing and selling kunu, manufacturers and hawkers receive training on proper hygiene practices and Hazard analysis of critical control points (HACCP) system ought to be used throughout the whole production process.